Formulation and Characterization of a Kinetically Stable Topical Nanoemulsion Containing the Whitening Agent Kojic Acid - Gan Yi Yun; Nur Azzanizawaty Yahya; Roswanira Abdul Wahab; Mariani Abdul Hamid (Universitas Gadjah Mada, 2021)
The research was carried out to synthesize a stable kojic acid (KA) encapsulated nanoemulsion as a whitening agent for topical skin usage. In this study, the oil-in-water (O/W) KA nanoemulsion was formulated using integrated low and high energy methods that combined ultrasonic and hot temperature inversion methods. Several different combinations of parameters were screened, viz. xanthan gum amount (1.0 to 2.0 g), kojic acid (KA) amount (0.5 to 1.5 g), and surfactant-to-water ratio (1:10.75 to 1:4.875), to prepare a stable KA nanoemulsion. The identified best parameters to design the O/W KA nanoemulsion were then subjected to different stability tests: storage and pH stability (freeze-thaw and centrifugal tests). Results revealed that the Trial 6 formulation, with the highest ratio of Tween 80 to water (1:4.875 v/v), yielded the best polydispersity index at 0.255 ± 0.006 with an average particle size of 90.57 ± 1.401 nm. The formulation retained the recommended pH range (pH 4.95–5.18) for topical skin applications within six-week storage under room condition. The nanoemulsions were also kinetically stable as proven by the absence of phase separation after the centrifugation, freeze-thaw cycle, and storage temperature (2 and 25 °C) tests, except at the 37 °C three-week extended storage. The results collectively showed that the formulated O/W KA nanoemulsion is suitable for topical application on human skin.